TMET-24. MITOCHONDRIAL AND GENE EXPRESSION CHANGES IN BRAIN TUMOR CELLS GROWN IN Β-HYDROXYBUTYRATE. (14th November 2022) - Almekkawi, Ahmad Kareem; Sheets, Rachelle; Werner, Brianna; Perryman, Richard; Singh, Indrapal; Karim, Mohammad; Frye, Richard; Syed, Nelofer; Scheck, Adrienne
Abstract: Malignant brain tumors are devastating diseases with poor outcomes. The search for more effective therapeutic combinations has led to investigation of the use of a therapeutic ketogenic diet (KD) as an adjuvant therapy based on the metabolic dysregulation that is a hallmark of cancer. KD sometimes results in extended survival, but like all cancer therapies the tumor eventually becomes resistant. Resistance can arise due to the "metabolic remodeling" of resistant cells due to limitations in nutrient availability and other signals from the tumor microenvironment. We are investigating the molecular and mitochondrial changes of tumor cells grown in β-hydroxybutyrate (BHB), the main ketone produced when following a therapeutic KD, to partially recapitulate the long-term effects of the KD on patients. Murine malignant glioma cells (GL261-luc2) were cultured long term in 2, 5 or 10mM BHB. The Agilent XFe96 Seahorse Analyzer was used to measure changes in cell metabolism. Epigenetic changes that occur in the mitochondria were interrogated using DNA methylation assays. Finally, we implanted BHB resistant glioma cells intracranially in mice and carried out RNAseq to determine the mechanisms by which these cells adapt. Seahorse analyses of GL261-luc2 cells grown in BHB demonstrated changes in several respiratory parameters including maximal respiration and reserve capacity. In addition, there is a statistically significant decrease in mitochondrial DNA methylation with increasing concentrations of BHB. RNAseq analysis of BHB resistant GL261 tumors showed changes in pathways related to mitochondrial translation and the electron transport chain. Our preliminary results show that the heterogeneity seen in these tumors is recapitulated in the various mitochondrial respiration parameters. Further, these may be altered as a consequence of BHB therapy. An understanding of the genetic and mitochondrial changes that occur when cells become resistant will lead to a more effective use of the KD as an adjuvant therapy.